Neuronal correlates of the visual-spatial processing measured with functional near-infrared spectroscopy in healthy elderly individuals. (November 2020) - Haberstumpf, Sophia; Seidel, Alexandra; Lauer, Martin; Polak, Thomas; Deckert, Jürgen; Herrmann, Martin J.
Abstract: Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI) are a globally rising issue. It is necessary to detect such diseases early to find strategies for prevention. Typically, patients with MCI or AD show deviant neuronal patterns, which could be detected early through brain imaging techniques enabling assumptions about pre-existing diseases. Functional Near-Infrared Spectroscopy (fNIRS) is an appropriate imaging method because of its easy and economical nature with hardly any drawbacks. An early measurable risk factor indicating neurodegenerative processes could be a deficit in visual-spatial processing, which is localized in the parietal cortex. In this study, we aimed to measure the hemodynamic response of the visual-spatial processing in the healthy elderly participants of our long-term Vogel Study with fNIRS during the clock-hand-angle-discrimination task (ADT) to deepen our understanding of healthy brain mechanisms. Our results revealed for our healthy sample a significantly increased neuronal brain activity with increasing task difficulties, namely from the long to the middle to the short clock hand during ADT and significantly higher activation in the right hemisphere compared to the left hemisphere as well as in the superior parietal cortex compared to the inferior parietal cortex. Additionally, our behavioral data demonstrated longer reaction times and more errors with an increasing task requirement. We, therefore, assume that visual-spatial processing can successfully be operationalized with fNIRS for healthy elderly people based on ADT. Further fNIRS analyses are planned to investigate pathological neuronal correlates of visual-spatial function in MCI or AD study participants. Highlights: Parietal cortex activation during visual-spatial tasks can be measured with fNIRS. Visual-spatial processing can be measured using angle discrimination tasks. Significant activation of the parietal cortex can be found in healthy elderly. Higher task requirement results in an increased (right-lateral) neuronal activity. Higher task requirement results in higher reaction times and more errors.